2017
DOI: 10.3390/su9020267
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Values-Based Supply Chain (VBSC) on Farm-Level Viability, Sustainability and Resilience: Case Study Evidence

Abstract: Abstract:The 'Agriculture of the Middle' (AotM) development paradigm emphasises that in order to survive, family farms must transition from a supply chain approach to a values-based supply chain (VBSC) approach, involving amendments to both product type and actor dynamics within the chain. This paper presents a qualitative case study of a beef co-operative integrated to a VBSC. We use an analytical framework of viability, sustainability and resilience to analyse impacts at farm-level. Our analysis highlights a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Revealing the intricacies of coordinated beef production and marketing, Hooks et al (2017aHooks et al ( , 2017b) present a study of US beef co-operative and the nature of contractual arrangements between the co-operative, processors and retailers. The authors found that a beef cooperative's integration to a values-based supply chain 6 (VBSC) involving contractual arrangements vertically between across-chain actors (e.g.…”
Section: Producer Organisationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Revealing the intricacies of coordinated beef production and marketing, Hooks et al (2017aHooks et al ( , 2017b) present a study of US beef co-operative and the nature of contractual arrangements between the co-operative, processors and retailers. The authors found that a beef cooperative's integration to a values-based supply chain 6 (VBSC) involving contractual arrangements vertically between across-chain actors (e.g.…”
Section: Producer Organisationsmentioning
confidence: 99%
“…The cooperative was integrated to a VBSC, which is consistent with the structure and objectives of POs and APOs, but IBOs in particular. Hooks et al (2017a), in a study of the US beef cooperative reported how integration to a VBSC with chain partners (processors and retailers) led to enhanced trust and transparency between chain partners. Also, producing premium beef products and setting prices based on cost of production (to cover costs at all levels of the chain led to fairer distribution of economic returns for chain partners.…”
Section: Adding Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Revealing the intricacies of coordinated beef production and marketing, previous research presents a study of US beef co-operative and the nature of contractual arrangements between the co-operative, processors and retailers [42,43]. The authors found that a beef cooperative's integration to a values-based supply chain (VBSC) involving contractual arrangements vertically between across-chain actors (e.g., the co-operative, processors and retailers) led to enhanced trust, transparency and profits for all chain partners.…”
Section: Associations Of Pos and Interbranch Organisationsmentioning
confidence: 99%
“…The cooperative was integrated to a VBSC, which is consistent with the structure and objectives of POs and APOs but IBOs in particular. The study of the US beef co-operative showed how integration to a VBSC with chain partners (processors and retailers) led to enhanced trust and transparency between chain partners [42]. Also, producing premium beef products and setting prices based on cost of production (to cover costs at all levels of the chain led to fairer distribution of economic returns for chain partners.…”
Section: Adding Valuementioning
confidence: 99%